Information system strategies: The South African context - Neil Duffy (South African Journal of Business Management, 1991)
Many studies of information systems (IS) Issues place IS strategy at the top of the list. In this article the development is sketched of IS strategy and then the relevant findings are summarised of a number of studies undertaken at the Wits Business School over the last five years which provide the South African context. From these studies it is possible to derive an information systems strategy profile of the respondent organisations and to trace the information systems Issues that have concerned them. It is interesting to note that some of these information systems Issues seem to have persisted through the years and seem likely to continue to do so.
Keywords: 650